Modelagem e simulação do controle da postura ereta humana quasi-estática com reflexos neuromusculares - Naves, Eduardo Lázaro Martins (2006)
This work presents a computer mathematical model of the human neuromusculoskeletal system specially designed to study the postural balance in standing. In addition to the extrafusal muscle tissue properties commonly used in traditional muscle models applied to study human movement and posture, this model includes two components physiologically important of postural control system: the intrafusal muscle tissue properties and intrinsic reflex responses provided by three neuromuscular organs (muscle spindles, Golgi tendon and Rhenshaw cells). The global model treats the body as a single-link inverted pendulum supported by a pair of muscle-reflex actuators (Winters, 1995) controlled by a proportional-integral-derivative controller. Model simulations were made with and without the contribution of the modelled reflex responses. The results were compatible with those presented in other investigations based on experimental data. In this manner, three fundamental properties of somatosensory feedback system were mathematically had been proven: (i) its anticipatory characteristic, (ii) its capacity to maintain alone the human body in standing posture and (iii) the incapacity of the body in supporting itself in that position in the absence of the modelled reflex responses. This model analysis allows one to conclude that the modelled reflex responses plays a fundamental role when a subject maintains an upright posture. This model can be used to formulate hypothesis about the origin of the feedback somatosensory deficits on human postural control in standing.